2022
DOI: 10.1111/ane.13634
|View full text |Cite
|
Sign up to set email alerts
|

Greater occipital nerve block for chronic migraine patients: A meta‐analysis

Abstract: Introduction Greater occipital nerve block (GONB) is a minimally invasive procedure frequently used in patients with chronic migraine (CM); however, the quality of the evidence supporting its use is still unknown. Therefore, we aimed to conduct a systematic review, meta‐analysis and quality assessment of GONB local anaesthetics combined or not with corticosteroids to prevent CM. Methods We searched Medline, Scopus and Web of Science up to October 2020. We included randomized control trials (RCT) and observatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 38 publications
(152 reference statements)
0
3
0
Order By: Relevance
“…Cuadrado et al (15) assessed the short-term clinical efficacy of GONB in chronic migraine patients and found it to be significantly superior to placebo in reducing the number of moderate to severe or any headache during the week following the injection. However, its effectiveness for the long-term prevention of CM lacks a good evidence base (16). Three previous placebocontrolled double-blind randomized trials of GONB in CM had methodological limitations and produced conflicting results (17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%
“…Cuadrado et al (15) assessed the short-term clinical efficacy of GONB in chronic migraine patients and found it to be significantly superior to placebo in reducing the number of moderate to severe or any headache during the week following the injection. However, its effectiveness for the long-term prevention of CM lacks a good evidence base (16). Three previous placebocontrolled double-blind randomized trials of GONB in CM had methodological limitations and produced conflicting results (17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%
“…A previous meta-analysis reported that local anesthetics could reduce headache frequency and intensity compared with placebo, but the addition of corticosteroids showed no additional benefits with limited evidence. [ 26 ] All GON blocks in our study were performed with 1.5 cc bupivacaine diluted in half with saline, which we routinely use in daily practice, and did not add corticosteroids. In a randomized, multicenter, double-blind, and placebo-controlled study with 84 patients with CM by Inan et al ,[ 27 ] GON block with a mixture of 1.5 mL of 0.5% bupivacaine and 1 mL of saline was superior to placebo and effective, safe, and cost-effective for the treatment of CM.…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis addressing the efficacy of chemical blockade (i.e., with a local anesthetic) of the greater occipital nerve in CM patients concluded that this method reduced both the frequency and intensity of headache compared to the placebo [ 132 ].…”
Section: Recommended Prophylactic Treatment Options In CMmentioning
confidence: 99%